Numerical analysis of construction of drainage system for precipitation waters - Gąska, Piotr (Budownictwo i Architektura / Civil and Architectural Engineering, 2013)
Progressive implements which make possible advanced geotechnical analysis, induced the author to verify previously accepted engineering solutions of construction of rain waters drainage system with the use of reinforced concrete walls and horizontal geogrids. The quantitative analysis of stress distribution in ground medium around the drainage system was performed in numerical model with the use of finite element method . This analysis confirmed previous – intuitive and qualitative - assumptions of the technical design. The application of reinforced concrete walls, transmission of ground lateral pressure to the soil below and the above drainage system, result in twofold reduction of horizontal components of ground stresses in area between reinforced walls and the drainage. The usage of two layers of geogrid over the drainage system made possible strain relief of this system (in the middle, the most sensitive zone) in vertical direction of about 75%.